Response-adapted omission of radiotherapy in children and adolescents with early-stage classical Hodgkin lymphoma and an adequate response to vincristine, etoposide, prednisone, and doxorubicin (EuroNet-PHL-C1): a titration study - Mauz-Körholz, Christine; Landman-Parker, Judith; Fernández-Teijeiro, Ana; Attarbaschi, Andishe; Balwierz, Walentyna; Bartelt, Jörg M; Beishuizen, Auke; Boudjemaa, Sabah; Cepelova, Michaela; Ceppi, Francesco; Claviez, Alexander; Daw, Stephen; et al. (Lancet oncology, 2023)
BACKGROUND: Children and adolescents with early-stage classical Hodgkin lymphoma have a 5-year event-free survival of 90% or more with vincristine, etoposide, prednisone, and doxorubicin (OEPA) plus radiotherapy, but late complications of treatment affect survival and quality of life. We investigated whether radiotherapy can be omitted in patients with adequate morphological and metabolic responses to OEPA. METHODS: The EuroNet-PHL-C1 trial was designed as a titration study and recruited patients at 186 hospital sites across 16 European countries. Children and adolescents with newly diagnosed stage IA, IB, and IIA classical Hodgkin lymphoma younger than 18 years of age were assigned to treatment group 1 to be treated with two cycles of OEPA (vincristine 1·5 mg/m2 intravenously, capped at 2 mg, on days 1, 8, and 15; etoposide 125 mg/m2 intravenously, on days 1-5; prednisone 60 mg/m2 orally on days 1-15; and doxorubicin 40 mg/m2 intravenously on days 1 and 15). If no adequate response (a partial morphological remission or greater and PET negativity) had been achieved after two cycles of OEPA, involved-field radiotherapy was administered at a total dose of 19·8 Gy (usually in 11 fractions of 1·8 Gy per day). The primary endpoint was event-free survival. The primary objective was maintaining a 5-year event-free survival rate of 90% in patients with an adequate response to OEPA without radiotherapy. We performed intention-to-treat and per-protocol analyses. The trial was registered at ClinicalTrials.gov (NCT00433459) and with EUDRACT, (2006-000995-33) and is completed. FINDINGS: Between Jan 31, 2007, and Jan 30, 2013, 2131 patients were registered and 2102 patients were enrolled onto EuroNet-PHL-C1. Of these 2102 patients, 738 with early-stage disease were allocated to treatment group 1. Median follow-up was 63·3 months (IQR 60·1-69·8). We report on 714 patients assigned to and treated on treatment group 1; the intention-to-treat population comprised 713 patients with 323 (45%) male and 390 (55%) female patients. In 440 of 713 patients in the intention-to-treat group who had an adequate response and did not receive radiotherapy, 5-year event-free survival was 86·5% (95% CI 83·3-89·8), which was less than the 90% target rate. In 273 patients with an inadequate response who received radiotherapy, 5-year event-free survival was 88·6% (95% CI 84·8-92·5), for which the 95% CI included the 90% target rate. The most common grade 3-4 adverse events were neutropenia (in 597 [88%] of 680 patients) and leukopenia (437 [61%] of 712). There were no treatment-related deaths. INTERPRETATION: On the basis of all the evidence, radiotherapy could be omitted in patients with early-stage classical Hodgkin lymphoma and an adequate response to OEPA, but patients with risk factors might need more intensive treatment. FUNDING: Deutsche Krebshilfe, Elternverein für Krebs-und leukämiekranke Kinder, Gießen, Kinderkrebsstiftung Mainz of the Journal Oldtimer Markt, Tour der Hoffnung, Menschen für Kinder, Mitteldeutsche Kinderkrebsforschung, Programme Hospitalier de Recherche Clinique, and Cancer Research UK.
Keywords: Doxorubicin; prednison; mladiství; mužské pohlaví; Hodgkin Disease; Vincristine; kvalita života; dítě; Child; Infant, Newborn; ženské pohlaví; novorozenec; doxorubicin; Humans; Prednisone; Etoposide; etoposid; vinkristin; Hodgkinova nemoc; Female; Quality of Life; Adolescent; lidé; Male